2016
DOI: 10.1155/2016/3240261
|View full text |Cite
|
Sign up to set email alerts
|

On the Anticataractogenic Effects of L‐Carnosine: Is It Best Described as an Antioxidant, Metal‐Chelating Agent or Glycation Inhibitor?

Abstract: Purpose. L-Carnosine is a naturally occurring dipeptide which recently gained popularity as an anticataractogenic agent due to its purported antioxidant activities. There is a paucity of research and conclusive evidence to support such claims. This work offers compelling data that help clarify the mechanism(s) behind the anticataract properties of L-carnosine. Methods. Direct in vitro antioxidant free radical scavenging properties were assayed using three different antioxidant (TEAC, CUPRAC, and DPPH) assays. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 36 publications
2
18
0
1
Order By: Relevance
“…The ability of EGCNPs to prevent protein glycation was determined by measuring the distinctive fluorescence of advanced glycation end products (AGEs) as previously reported [24]. Briefly, two solutions of bovine serum albumin (BSA, 10 mg/mL) and Dglucose (10 mg/mL) were separately made in PBS (pH = 7).…”
Section: Measuring Antiglycation Properties Of Egcnps On Bsa and Bovine α-Crystallinmentioning
confidence: 99%
“…The ability of EGCNPs to prevent protein glycation was determined by measuring the distinctive fluorescence of advanced glycation end products (AGEs) as previously reported [24]. Briefly, two solutions of bovine serum albumin (BSA, 10 mg/mL) and Dglucose (10 mg/mL) were separately made in PBS (pH = 7).…”
Section: Measuring Antiglycation Properties Of Egcnps On Bsa and Bovine α-Crystallinmentioning
confidence: 99%
“…These glycation reactions serve as the initial step in the development of diabetic pathologies (Hipkiss et al, 1995). In a study by Abdelkader et al (2016), carnosine was shown to have effective anti-glycation activity in cultured porcine lenses and human lens epithelial cell models. Even in the absence of a diabetic condition, the use of carnosine as a supplement may also help reduce glycosylated damage on lens redox glutathione system.…”
Section: Heath Benefitsmentioning
confidence: 99%
“…Carnosine was selected due to its established antioxidant, free radical scavenging, antiinflammatory and wound-healing properties [12][13][14]. This dipeptide is widely distributed in muscles and nervous tissues, where it plays an important protective function [15].…”
Section: Introductionmentioning
confidence: 99%